2021
DOI: 10.48550/arxiv.2109.05617
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinism and invariant measures for diffusing passive scalars advected by unsteady random shear flows

Abstract: Here we study the long time behavior of an advection-diffusion equation with a general time varying (including random) shear flow imposing no-flux boundary conditions on channel walls. We derive the asymptotic approximation of the scalar field at long times by using center manifold theory. We carefully compare it with existing time varying homogenization theory as well as other existing center manifold based studies, and present conditions on the flows under which our new approximations give a substantial impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…For example, the diffusing diffusivity model models the diffusivity as a function of OU process [11,20,43]. The study of dynamo [4,49] and the passive-scalar decay problem [46,15,1] concerns the renewing process. The modeling of Black-Scholes market [19] involves fractional Brownian motion.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the diffusing diffusivity model models the diffusivity as a function of OU process [11,20,43]. The study of dynamo [4,49] and the passive-scalar decay problem [46,15,1] concerns the renewing process. The modeling of Black-Scholes market [19] involves fractional Brownian motion.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Center manifold theory is a powerful tool to handle the scalar transport problem in bounded domain [32], and to derive the self-similarity solution of stochastic nonlinear diffusion reaction equation [47]. A recent study [15] has shown that, for the scalar transport problem in channel domain, the center manifold theory yields an effective equation with variable coefficients, which yields a long time limiting distribution of the random scalar field in the white noise case. Numerical simulation showed that this approximation performs better than the result from the standard homogenization method at an intermediate time scale.…”
Section: Conclusion and Discussionmentioning
confidence: 99%